A miskolci Bosch új generációs toborzást támogató eszközei - Masa, Beáta; Alexa, Mariann (Észak-magyarországi Stratégiai Füzetek, 2026)
In 2018, the recruitment of Bosch’s workforce in Miskolc underwent a major transformation. The background is today’s changing business environment, drastic changes in purchasing patterns, the emergence of new generations on the labor market, and aggressive marketing strategies by market players, while our factory size and complexity is constantly increasing. Reactions in innovation and other business applications are no longer fast enough. As with competitive sports, the movement of competitors and the market must be anticipated and acted upon. This is the ability to react quickly and intelligently - the so-called. Agility - increasingly the difference between success and failure. This is what made the decisions we made last year. As the largest employer of the city of Miskolc, we are constantly present in the labor market, but at the same time, we felt that in an accelerated world we too needed to accelerate and modernize our recruitment process. The transformation in recruitment has taken into account the Bosch Global Principle: this is the "Candidate first" philosophy, ie the "candidate first". We followed this principle from the first steps to the recruitment process, from branding and advertising, building a cloud-based application tracking system (ATS), developing innovative interviewing technology, to feedback and onboarding.